Caplacizumab as an add-on therapy in a 7-year-old girl with exacerbated immune-mediated thrombotic thrombocytopenic purpura, a case report and literature review - Chavaz, Lara; Cimasoni, Laurent; Kremer Hovinga, Johanna A.; Coppo, Paul; Ansari, Marc (Frontiers in Pediatrics, 2024)
The cornerstone treatment for immune-mediated thrombotic thrombocytopenic purpura (iTTP) in children is a combination of therapeutic plasma exchange (TPE), corticosteroids and rituximab. Caplacizumab is an anti-von Willebrand factor (VWF) NANOBODY® molecule approved as a frontline therapy of iTTP for adults and children ≥12 years old. Using caplacizumab in children <12 years old remains a grey area based on recommendations but with no marketing authorization. We report the first case of a pediatric patient with iTTP successfully treated with caplacizumab dose adjustment of 5 mg daily based on ADAMTS13 activity. We also review all published cases of iTTP in children <12 years old treated with caplacizumab. This is a 7-year-old girl with a clinical thrombotic microangiopathy, in absence of diarrhea and kidney injury. With a French score of 2 and a PLASMIC score of 7 (high risk), the diagnosis of TTP was suspected and later confirmed by severely low ADAMTS13 activity (<5%). Immune-mediated TTP was distinguished from the congenital one due to the presence of functional ADAMTS13 inhibitor. Daily TPE and intravenous corticosteroids were started on day 0 (D0). Rituximab was added on D4, and due to refractoriness under daily TPE we considered off-label administration of caplacizumab from D12. A clinical answer, with a significant increase of the platelet count was observed within 48 hours. A complete ADAMTS13 recovery was reached on D62. No major adverse events were observed during the treatment. She was discharged from hospital over three months ago with platelet count still within norms. In the literature, we identified a total of four case reports describing 5 iTTP patients <12 years-of-age treated with caplacizumab, with a 100% success and tolerability. These published data attest the efficacy and safety of the systematic use of caplacizumab and rituximab as frontline therapy in pediatric iTTP under 12 years-of-age. Therefore, prospective data are needed to support commercial authorization of caplacizumab in this sub-population. The close monitoring of ADAMTS13 activity is particularly of interest among children to limit the number of caplacizumab injections.